2017
DOI: 10.1371/journal.pone.0178601
|View full text |Cite
|
Sign up to set email alerts
|

Multiple extracellular vesicle types in peritoneal dialysis effluent are prominent and contain known biomarkers

Abstract: Peritoneal dialysis inevitability results in activation of inflammatory processes and its efficiency is highly variable between patients. An improved method to isolate biomarkers and study pathophysiological mechanisms in peritoneal dialysis effluent (PDE) is expected to be of much benefit for the development of this treatment approach and help with patient management. Extracellular vesicles (EVs) are released as part of normal cellular processes. Their proteome is expected to reflect both type and health of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 45 publications
3
22
0
Order By: Relevance
“…Later, Corciulo and co-workers [99] described aquaporin (AQP1)-containing exosomes in PDE as biomarkers of dialysis efficiency. AQP-1 had also been found in samples from Pearson's study [98]. On the basis of a study of 30 patients, the authors found that levels of AQP1 in PDE-EVs positively correlated with the efficiency of PD.…”
Section: Extracellular Vesicles In Pdementioning
confidence: 92%
See 2 more Smart Citations
“…Later, Corciulo and co-workers [99] described aquaporin (AQP1)-containing exosomes in PDE as biomarkers of dialysis efficiency. AQP-1 had also been found in samples from Pearson's study [98]. On the basis of a study of 30 patients, the authors found that levels of AQP1 in PDE-EVs positively correlated with the efficiency of PD.…”
Section: Extracellular Vesicles In Pdementioning
confidence: 92%
“…Only a few weeks later, Pearson et al published another study on the proteomics of EVs and PD [98]. In this case, samples were segregated in terms of EV purification, as some of them were enriched by ultracentrifugation (UC) and some others by UC plus an additional size exclusion chromatography enrichment.…”
Section: Extracellular Vesicles In Pdementioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the large number of assumptions about the nature of the particle size distribution (e.g., mono- or multi-modal) that is necessary for appropriate fitting of the measured intensity correlation function, DLS is best suited for quantitative analysis of relatively monodisperse samples. In a biological and biomedical context, it is often applied for determining the size of isolated EVs and the synthetic variants (e.g., liposomes) [92,93,94,95]. However, because DLS detects all scattering objects in solution, it has limited utility in the analysis of minimally-processed biofluids.…”
Section: Common Methods For Ev Quantification and Characterizationmentioning
confidence: 99%
“…A literature search in NCBI Pubmed utilizing the query string (proteomics AND peritoneal dialysis) OR (proteome AND peritoneal dialysis) OR (proteomics AND peritoneal fluid) OR (proteome AND peritoneal fluid) OR (proteomics AND peritoneal effluent) OR (proteome AND peritoneal effluent) on Oct 26, 2017 resulted in 83 hits. These were restricted to clinical peritoneal dialysis effluent from humans, to return only 15 studies ( 7 19 , 38 , 39 ) of which two were excluded because they focused solely on the exosomal fraction ( 38 , 39 ) and one did not provide any protein accessions ( 19 ), resulting in 12 studies and 171 unique proteins for analysis ( supplemental Table S1 ) ( 7 18 ). Manual query of protein names presented by Zavvos et al ( 19 ) yielded 19 protein names not contained in the 171, of which 11 were unreviewed and 8 were reviewed entries in UniProt.…”
Section: Methodsmentioning
confidence: 99%